Psikoedukasi Mengurangi Perilaku Kenakalan Remaja pada Siswa di Sanggar Kegiatan Belajar Kota X - Moch Fatkur Rozy; Herlan Pratikto; Tatik Imadatus Sa’adati (CV. Doki Course and Training, 2026)
Juvenile delinquency is a psychosocial problem commonly emerging during adolescence and significantly affecting educational continuity and psychological well-being. This study aimed to explore the psychological dynamics of juvenile delinquency among students at a nonformal education center (Sanggar Kegiatan Belajar/SKB) in City X and to evaluate the effectiveness of a community-based psychological intervention. The assessment employed interviews, delinquency questionnaires, the Forer Sentence Completion Test (FSCT), and Focus Group Discussions (FGD) involving students, teachers, and parents. The findings revealed maladaptive thinking patterns, emotional instability, and impaired social functioning influenced by individual, family, and school-related factors. A group-based psychoeducational intervention incorporating cognitive restructuring, self-identity strengthening, and interpersonal skills training was conducted across three sessions. Evaluation results indicated improvements in emotional regulation, self-acceptance, communication skills, and adaptive decision-making. However, sustained behavioral recovery requires continuous support from families, schools, and the broader community to maintain long-term positive outcome.